Performance of concrete containging metakaolin as cement replacement material - Ong, Chee Huat (2006)
Concrete is probably the most extensively used construction material in the world. However, environmental concerns both in terms of damage caused by the extraction of raw material and CO2 emission during cement manufacture have brought pressures to reduce cement consumption by the use of supplementary materials. The utilization of calcined clay, in the form of metakaolin (MK) in concrete has received considerable attention in recent years. On this matter, a study has been conducted to look into the performance of metakaolin as cement replacement material in concrete. The study focuses on the compressive strength performance of the blended concrete containing different percentage of metakaolin. The cement is replaced accordingly with the percentage of 5 %, 10%, 15%, 20% and 30% by weight. Concrete cubes are tested at the age of 1, 3, 7, and 28 days. In addition, the effect of calcination temperature to the strength performance is included in the study. Finally, the strength performance of metakaolin-concrete is compared with the performance of concrete blended with silica fume and slag. The results show that the strength development of concrete blended with metakaolin is enhanced. It was found that 10% replacement appears to be the optimum replacement where concrete exhibits enhanced compressive strength at all ages comparable to the performance of SF and GGBS. The study also reveals that optimum calcination temperature of 750Â°C is important to improve the performance of metakaolin-concrete